The in vitro ToxTracker and Aneugen Clastogen Evaluation extension assay as a tool in the assessment of relative genotoxic potential of e-liquids and their aerosols. (18th March 2021) - Czekala, Lukasz; Chapman, Fiona; Simms, Liam; Rudd, Kathryn; Trelles Sticken, Edgar; Wieczorek, Roman; Bode, Lisa Maria; Pani, Jutta; Moelijker, Nynke; Derr, Remco; Brandsma, Inger; Hendriks, Giel; et al.
Abstract: In vitro (geno)toxicity assessment of electronic vapour products (EVPs), relative to conventional cigarette, currently uses assays, including the micronucleus and Ames tests. Whilst informative on induction of a finite endpoint and relative risk posed by test articles, such assays could benefit from mechanistic supplementation. The ToxTracker and Aneugen Clastogen Evaluation analysis can indicate the activation of reporters associated with (geno)toxicity, including DNA damage, oxidative stress, the p53-related stress response and protein damage. Here, we tested for the different effects of a selection of neat e-liquids, EVP aerosols and Kentucky reference 1R6F cigarette smoke samples in the ToxTracker assay. The assay was initially validated to assess whether a mixture of e-liquid base components, propylene glycol (PG) and vegetable glycerine (VG) had interfering effects within the system. This was achieved by spiking three positive controls into the system with neat PG/VG or phosphate-buffered saline bubbled (bPBS) PG/VG aerosol (nicotine and flavour free). PG/VG did not greatly affect responses induced by the compounds. Next, when compared to cigarette smoke samples, neat e-liquids and bPBS aerosols (tobacco flavour; 1.6% freebase nicotine, 1.6% nicotine salt or 0% nicotine) exhibited reduced and less complex responses. Tested up to a 10% concentration, EVP aerosol bPBS did not induce any ToxTracker reporters. Neat e-liquids, tested up to 1%, induced oxidative stress reporters, thought to be due to their effects on osmolarity in vitro . E-liquid nicotine content did not affect responses induced. Additionally, spiking nicotine alone only induced an oxidative stress response at a supraphysiological level. In conclusion, the ToxTracker assay is a quick, informative screen for genotoxic potential and mechanisms of a variety of (compositionally complex) samples, derived from cigarettes and EVPs. This assay has the potential for future application in the assessment battery for next-generation (smoking alternative) products, including EVPs.